Savoir et pouvoir dans les œuvres juridiques d’Alphonse X : une synthèse et une hypothèse - Daniel A. Panateri (Atalaya)
The purpose of this study is to analyse the narrative of law present in the legal work of Alfonso X, in particular in the Siete Partidas. In this work, the narrative in question is centred on the concept of knowledge as a structuring element of the image of power, an image reflected in the legal work. This image of power is also produced by the text itself. The proposed analysis will therefore consist of a presentation of different cases in the above-mentioned work. The aim will be to discuss the various modes of narrative action of the concepts involved in the construction of this narrative and the commonalities between these concepts. These imply the existence of an Alphonsine conceptual system in which the use of the notions of knowledge and power leads to differences that respond to specific strategies within the text itself. These differences produce, however, and at the same time, a strong sense of unity, reinforced by phenomena of aggregation and complementarity.